Audio Signal Processing - Vesa Välimäki (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Audio signal processing is a highly active research field where digital signal processing theory meets human sound perception and real-time programming requirements. It has a wide range of applications in computers, gaming, and music technology, to name a few of the largest areas. Successful applications include, for example, perceptual audio coding, digital music synthesizers, and music recognition software. The fact that music is now often listened to using headphones from a mobile device leads to new problems related to background noise control and signal enhancement. Developments in processor technology, such as parallel computing, are changing the way signal-processing algorithms are designed for audio. Topics covered, but were not limited to, the following areas: - Audio signal analysis - Music information retrieval - Enhancement and restoration of audio - Audio equalization and filtering - Audio effects processing - Sound synthesis and modeling - Audio coding - Sound capture and noise control - Sound source separation - Room acoustics and spatial audio - Signal processing for headphones and loudspeakers - High-performance computing in audio